2008
DOI: 10.1152/physiolgenomics.00191.2007
|View full text |Cite
|
Sign up to set email alerts
|

Aging alters gene expression of growth and remodeling factors in human skeletal muscle both at rest and in response to acute resistance exercise

Abstract: The purpose of this investigation was to compare expression of genes that function in inflammation and stress, cell structure and signaling, or remodeling and growth in skeletal muscle of young (32 ± 7 yr, n = 15) and elderly (72 ± 5 yr, n = 16) healthy subjects before and after a bout of resistance leg exercises. A real-time RT-PCR method was used to screen 100 transcripts in v. lateralis biopsies obtained before and 72 h postexercise. The screen identified 15 candidates for differential expression due to agi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 67 publications
(71 reference statements)
6
67
0
1
Order By: Relevance
“…32 However, in other tissue, there appears to be a stronger relationship between age and MMP dysregulation. 28,34 In cardiac tissue, exercise training seemingly protects against age-associated reductions in active MMP-1, MMP-2 and MT1-MMP in a rodent model. Regular physical activity attenuates elevations in TIMP-1 that were detected in aging versus young rats.…”
Section: Discussionmentioning
confidence: 99%
“…32 However, in other tissue, there appears to be a stronger relationship between age and MMP dysregulation. 28,34 In cardiac tissue, exercise training seemingly protects against age-associated reductions in active MMP-1, MMP-2 and MT1-MMP in a rodent model. Regular physical activity attenuates elevations in TIMP-1 that were detected in aging versus young rats.…”
Section: Discussionmentioning
confidence: 99%
“…results suggest that adult muscles have ϳ2-3 times the minimum concentration of myostatin that is needed to restrain muscle growth. Thus, a modest reduction in myostatin expression, such as the reduction often observed after exercise (8,12,14,15,24,31,37), might not be sufficient to promote muscle hypertrophy by itself. This conclusion is supported by the observation that many subjects with reduced (ϳ50%) myostatin expression after strength training do not have muscle fiber hypertrophy (15).…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have demonstrated that resistance training reduces myostatin expression generally in the 20 -50% range (8,12,14,15,24,31,37). One of these studies indicated that the increase in muscle mass induced by such exercise correlated with the magnitude of suppression of myostatin mRNA expression (12), whereas another study did not support such a correlation (15).…”
mentioning
confidence: 99%
“…a-Cardiac actin (Actc1) expression has been shown to be regulated during muscle regeneration following trauma from pathologic diseases that appears characteristic of activated satellite cells and regenerating myofibers (Dennis et al, 2008). On day 10, Actc1 was significantly increased with both the high-and low-frequency doses of FST, whereas on day 14 it was only significant with the high-frequency dose, producing a 3.7-fold increase (Fig.…”
Section: Follistatin As a Novel Therapeutic For Muscle Regenerationmentioning
confidence: 95%